2015
DOI: 10.1002/cphc.201500459
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of the Electronic Properties of Armchair Graphene Nanoribbons through Functionalization: Theoretical Study of 1Δg O2 Border Addition

Abstract: We report the results of a DFT study of the border oxidation by (1) Δg O2 of molecular models of armchair graphene nanoribbons (a-GNRs). The aim of this work is to propose a new method, as an alternative or complementary method to the tuning of the size, to modify the electronic properties of a-GNRs. Here, we investigate modification of the HOMO and LUMO energies, which are some of the most important parameters to be controlled in the design of organic electronic devices. We study the oxidation reaction mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…These trends of the frontier orbital energies confirm the results we obtained for the molecular models. In the previous work, we observed a cumulative effect on increasing the number of couples of vicinal dialdehydic groups. This effect was not fully additive and we presume this was due to the limited dimensions of the molecular models.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…These trends of the frontier orbital energies confirm the results we obtained for the molecular models. In the previous work, we observed a cumulative effect on increasing the number of couples of vicinal dialdehydic groups. This effect was not fully additive and we presume this was due to the limited dimensions of the molecular models.…”
Section: Resultsmentioning
confidence: 78%
“…Because of the usage of molecular aromatic precursors, the latter techniques leads to the preparation of a ‐GNRs with all border sp 2 carbon bound to hydrogen atoms . In a previous work we have shown that the reaction of molecular models of these a ‐GNRs with singlet dioxygen ( 1 Δ g O 2 ) produces a decoration of their border with vicinal dialdheydic groups (Fig. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation